Kepemimpinan Demokratis-Transformasional dan Manajemen Adaptif dalam Memperkuat Kinerja Guru di Era Digital - Wahyu Widodo; Muh Hanif; Novan Ardy Wiyani (Universitas Sarjanawiyata Tamansiswa, 2026)
Digital transformation in education requires schools to develop adaptive leadership and managerial systems. This study aims to analyze the practices of democratic–transformative leadership and adaptive managerial approaches, as well as their impact on teacher performance at SDN 2 Kejobong in the digital era. The research employed a qualitative approach with data collected through interviews, participatory observations, and documentation. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing verified through source triangulation. The findings indicate that democratic–transformational leadership is implemented through two-way communication, teacher involvement in decision-making, the provision of space for innovation, and the establishment of PLC (Professional Learning Communities). The adaptive managerial system is strengthened through the use of digital platforms, application-based coordination, and the provision of ICT facilities. The integration of these two aspects significantly enhances teachers’ digital competence, work motivation, instructional innovation, and professional responsibility.